The Influence of Promotion, Brand Image, and Product Quality on Purchase Decisions at Star-Rated Hotel Restaurants in Batam - Nur Alin, Putri; Sukati, Inda (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The hotel industry in Batam continues to grow alongside the development of tourism and business sectors. Five-star hotel restaurants play an essential role in attracting consumers, particularly millennials and Generation Z, who prioritize experiential dining. This study aims to analyze the influence of promotion, brand image, and product quality on purchasing decisions at five-star hotel restaurants in Batam. This research applies a quantitative approach with an associative causal research design. A total of 100 respondents were selected using a nonprobability sampling technique with a convenience sampling approach. Data were collected through a Likert-scale questionnaire and analyzed using SPSS version 25, including validity testing, reliability testing, classical assumption testing, and multiple regression analysis. The findings indicate that promotion, brand image, and product quality have a positive and significant effect both partially and simultaneously on purchasing decisions. Product quality is identified as the most influential factor in purchasing decisions. The coefficient of determination (R²) value of 0.635 shows that the three variables explain 63.5% of the variance in purchase decisions. The study concludes that integrated marketing strategies supported by strong brand image and consistent product quality are essential to enhance consumer purchasing decisions in five-star hotel restaurants in Batam.